Influence of global slenderness and sliding pallets on seismic design of steel storage racks: a sensitivity analysis (2022)
In this research, the influence of global slenderness and sliding pallets factor on the seismic design of steel storage racks are assessed. Variations in span length, the height of storage levels, live load, and percentage of live load considered in the seismic mass are studied for different levels of seismic zone and soil type. The models were designed according to the Chilean Code NCh2369. Subsequently, a global sensitivity analysis was developed to analyze the influence of each studied parameter in the seismic design response in terms of fundamental period, drift, and base shear from a response spectral analysis approach. A total of 12000 simulations were performed. Two-hundred additional models were performed to evaluate the variation of seismic mass in the structural response. Results indicate a significant influence of live loads and seismic mass on steel racks designed for soft soils and unbrace conditions. The stiffness also modifies the performance of the racks, mainly in models using braces in the down-aisle direction and cross-aisle direction. In these cases, the seismic mass factor does not have a strong influence on structural response in comparison to the global slenderness